Cloud Properties Observed From the Surface and by Satellite at the Northern Edge of the Southern Ocean. Issue 1 (9th January 2018) - Alexander, S. P.; Protat, A.
Abstract: A Raman depolarization lidar was deployed at Cape Grim, Australia (40.7°S, 144.7°E), at the northern edge of the Southern Ocean from July 2013 to February 2014 from which we determine cloud boundaries, cloud phase, ice virga, and cloud effective top heights. We compare surface‐based lidar with results from the raDAR/liDAR (DARDAR) data set within 1, 000 km of Cape Grim. DARDAR combines information from the CloudSat and Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) instruments. We extract single‐layer clouds that are sufficiently thin for signal to be present on the farside of the cloud and which have a liquid cloud top phase. These conditions maximize the likelihood that both surface‐based lidar and DARDAR are observing the full vertical extent of the same clouds. Differences in low‐level cloud occurrence frequencies for these single‐layer clouds reveal that DARDAR underestimates cloud at 0.2–1.0 km altitude by a factor of 3 compared with the surface‐based lidar. When multiple cloud decks are present, the underestimate in this altitude region is around 2.5 times. Heterogeneous glaciation observed by the Cape Grim lidar in midlevel stratiform supercooled water clouds is similar to that reported by previous surface‐based observations adjacent to the Southern Ocean, with half of these clouds precipitating ice at cloud top temperatures of −20°C. This transition occurs around −15°C in the DARDAR data set, and this difference is likely due to the reduced sensitivity of surface‐based lidar in detecting precipitating ice compared with what a surface‐based radar could observe. Key Points: We quantify the fraction of low‐level clouds using lidar and the DARDAR satellite data product at the northern edge of the Southern Ocean DARDAR underestimates low‐level cloud occurrence (0.2‐1.0 km altitude) by a factor of 3 compared with surface lidar A 5°C difference between lidar and DARDAR T at which half the supercooled clouds glaciate is consistent with NH results.